Analisis bibliometrik : Kecemasan akademik - Akmala, Nida Azkia (PSYCOMEDIA : Jurnal Psikologi, 2024)
This study aims to analyze research trends related to academic anxiety in late adolescents and early adults through a bibliometric approach. Research data was collected from published articles on Google Scholar during the period 2020-2024 using the keywords “Academic Anxiety” and “Academic Anxiety." Analysis was conducted using the VOSviewer application to visualize research trends, relationships between variables, and author contributions. The results showed an increase in publications related to academic anxiety, with a primary focus on variables such as academic stress, self-efficacy, academic procrastination, and the impact of the COVID-19 pandemic. Visualization findings showed key themes such as the influence of academic stress, the role of self-efficacy on achievement, and the impact of technology on learner well-being. Although this study has limitations in data screening, the results provide a roadmap for future research to explore new topics and develop more effective intervention strategies.